Menstrual phase and postmatch perceptual recovery responses for naturally menstruating football players - Brown, G; Fullagar, H; Duffield, R. (International Journal of Sports Physiology and Performance, 2025)
Purpose: To explore the influence of menstrual phase on postmatch perceptual responses and the time course of recovery for professional footballers.